Pengaruh Beban terhadap Prediksi Umur Fatik Rangka Meja Kerja Balai LAPAN Garut Menggunakan Ansys Workbench - Wibawa, Lasinta Ari Nendra; Diharjo, Kuncoro (JTM-ITI (Jurnal Teknik Mesin ITI), 2020)
The study examines the effect of the load on fatigue life prediction of a workbench frame using the finite element method. The design of the workbench frame uses Autodesk Inventor Professional 2017, while finite element analysis uses Ansys Workbench. The workbench frame is subjected to loads 150, 175, 200, and 225 kg with a fully-reserved type of loading. Fatigue life prediction using Gerber's mean stress theory. The material of the workbench frame using Aluminum alloy 6061. The simulation results show that the workbench frame has a minimum fatigue life for loads of 150, 175, 200, and 225 kg, respectively 1 x 108, 6.61 x 107, 1.69 x 107, and 4.09 x 106 cycles. Whereas the minimum safety factor for fatigue life is 150, 175, 200, and 225 kg, respectively 1.395; 1,196; 1,046; and 0.930. It shows the workbench frame can withstand the fatigue life to a minimum of 107 cycles for a load of 150, 175, and 200 kg because it has a safety factor of more than 1. While for the 225 kg load, the workbench frame fails to reach a minimum age of 107 cycles due to fatigue life prediction is only 4.09 x 106 cycles with a safety factor of less than 1, which is 0.930.